Caribou Feeding Sites in Relation to Snow Characteristics in Northeastern Alaska - LaPerriere, Arthur J.; Lent, Peter C. (ARCTIC, 1977)
Caribou select areas of relatively shallow snow for winter feeding, and do so on at least two levels: broad area and microsite. They do not normally select sites with snow-packs having mean integrated Ram hardness values in excess at 85. However, in areas of relatively shallow hard-packed snow, which is easily fractured into slab-like pieces, they can obtain access to vegetation with less expenditure of energy than Ram hardness values alone would suggest. Alpine feeding areas in the Porcupine Lake basin of northeastern Alaska had this type of snow-pack in the winter of 1972-73. In typical taiga winter range, caribou use areas where the snow depth is less than 50 centimetres.